2013
DOI: 10.1128/jvi.02510-12
|View full text |Cite
|
Sign up to set email alerts
|

An Endothelial Cell-Specific Requirement for the UL133-UL138 Locus of Human Cytomegalovirus for Efficient Virus Maturation

Abstract: Human cytomegalovirus (HCMV) infects a variety of cell types in humans, resulting in a varied pathogenesis in the immunocompromised host. Endothelial cells (ECs) are considered an important target of HCMV infection that may contribute to viral pathogenesis. Although the viral determinants important for entry into ECs are well defined, the molecular determinants regulating postentry tropism in ECs are not known. We previously identified the UL133-UL138 locus encoded within the clinical strain-specific ULb= regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
62
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(74 citation statements)
references
References 91 publications
(139 reference statements)
10
62
2
Order By: Relevance
“…The rescue of these phenotypes in 5/8 STOP infection (Fig. 6D) is consistent with our previously reported TEM analysis, where no defect in the maturation of mature virions in fibroblasts infected with UL133/8 NULL virus was detected (42). While the standard deviations associated with this quantification are large and overlapping due to the variation in the number of virions present in each micrograph counted (range, 10 to 150), the differences observed for UL135 STOP infection relative to WT infection were statistically significant.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…The rescue of these phenotypes in 5/8 STOP infection (Fig. 6D) is consistent with our previously reported TEM analysis, where no defect in the maturation of mature virions in fibroblasts infected with UL133/8 NULL virus was detected (42). While the standard deviations associated with this quantification are large and overlapping due to the variation in the number of virions present in each micrograph counted (range, 10 to 150), the differences observed for UL135 STOP infection relative to WT infection were statistically significant.…”
Section: Resultssupporting
confidence: 80%
“…6). We recently demonstrated that while the UL133/8 locus was required for virus maturation in endothelial cells, a virus lacking the entire UL133/8 locus, UL133/ 8 NULL , exhibited no defects for virus maturation in fibroblasts (42). However, the results reported here suggest that UL135 is required for maturation when UL138 is expressed.…”
Section: Discussioncontrasting
confidence: 54%
“…So far, however, little is known about the functions exerted by viral tropism factors that act at a postentry stage and regulate, in a cell type-specific manner, subsequent stages of the virus replication cycle. In addition to the HCMV US20 and MCMV M45 (47) proteins, two other HCMV proteins were recently reported to contribute to HCMV tropism in endothelial cells by regulating post-immediate-early phases in the viral replication cycle (48,49,50). In these studies, the UL135 and UL136 proteins encoded within the UL133-to-UL138 locus of a clinical strain of the virus (48) were found to be required for efficient HCMV replication in primary endothelial cells (50).…”
Section: Discussionmentioning
confidence: 95%
“…In addition, in cells infected with a pUL71-deficient virus, viral proteins that normally associate with the cVAC are mislocalized (21). (vi) cVACs form in cells infected with highly passaged laboratory strains of HCMV that lack some genes present in wild-type viruses (4, 5, 8-15, 17, 20-23), as well as after infection with a low-passage-number virus that carries a nearly complete complement of HCMV genes (24). Interestingly, an HCMV locus spanning UL133 to UL138 is required for cVAC development in human microvascular endothelial cells, but not in embryonic lung fibroblasts (24), indicating that cell-specific viral factors can be involved.…”
mentioning
confidence: 99%
“…(vi) cVACs form in cells infected with highly passaged laboratory strains of HCMV that lack some genes present in wild-type viruses (4, 5, 8-15, 17, 20-23), as well as after infection with a low-passage-number virus that carries a nearly complete complement of HCMV genes (24). Interestingly, an HCMV locus spanning UL133 to UL138 is required for cVAC development in human microvascular endothelial cells, but not in embryonic lung fibroblasts (24), indicating that cell-specific viral factors can be involved. (vii) In addition to protein regulators of cVAC biogenesis, the HCMV microRNAs (miRNAs) miR UL112-1, US5-1, and US5-2 target mRNAs of several host proteins involved in regulation of the cellular secretory apparatus (25).…”
mentioning
confidence: 99%